ANALISIS FAKTOR PENDUKUNG DAN PENGHAMBAT IMPLEMENTASI KURIKULUM MERDEKA DI MADRASAH IBTIDAIYAH SWASTA PROVINSI JAMBI - Umil Muhsinin; Kiki Fatmawati; Bheta Adi Laelia (Cerdas Proklamator, 2025)
The implementation of Merdeka Curriculum in private Madrasah Ibtidaiyah in Jambi Province faces its own complexities given the characteristics of this educational institution which must integrate the national curriculum with the religious curriculum. This study aims to analyze the supporting and inhibiting factors for the implementation of Merdeka Curriculum in Private Madrasah Ibtidaiyah (MIS) in Jambi Province. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included madrasah heads, teachers, parents, and students from six MIS in Jambi Province, namely MIS Nurul Hidayah Jambi City, MIS An-Nizham Jambi City, MIS Nurul Yaqin Muaro Jambi, MIS Raudhatul Ma'Arif Muara Bungo, MIS Nurul Iman Muaro Jambi, and MIS Tarbiyatul Mubtadin Rambahan Tebo Regency. Data analysis refers to the research design of Miles, Huberman, and Saldana including data collection, data reduction, data presentation, and conclusion drawing. The results showed that the supporting factors for the implementation of Merdeka Curriculum in Jambi Province MIS include: (1) the commitment of the madrasah head in providing moral and material support; (2) the commitment of teachers in attending training and preparing learning tools; (3) parent support in participating in learning activities; and (4) support from the Ministry of Religious Affairs through KMA policy No. 347 of 2022 and KMA No. 450 of 2024. The inhibiting factors include: (1) limited facilities and infrastructure, especially technological devices, flexible learning spaces, internet access, and learning books; (2) teacher competency gaps in implementing student-centered learning and digital skills; and (3) limited budget for procuring learning resources and teacher training. These findings contribute to a comprehensive understanding of the dynamics of implementing Merdeka Curriculum in private madrasahs with distinctive characteristics and challenges.